Evaluation of cytogenetic and y chromosome microdeletion analyzes in infertile cases - Degirmenci, Banu; Solak, Mustafa; Yildiz, Saliha Handan; Erdogan, Mujgan Ozdemir; Elmas, Muhsin; Fistik, Tevhide (Elsevier Science Bv, 2019)
Objective: The aim of our study is to determine the frequency of chromosome abnormalities and Y chromosome microdeletions which are the causes of primary infertility, in Afyonkarahisar. Materials and methods: Cytogenetic analysis results of 504 infertile cases (217 women and 287 men) and Y chromosome microdeletion analysis results of 144 infertile men who had been referred to our department due to primary infertility or IVF failure between the years 2011-2016 were evaluated retrospectively. Results: The incidence of chromosomal abnormalities in 504 primer infertile cases was 4.96%. Chromosomal abnormalities were seen in 2.3% of 217 infertile women and 6.96% of 287 infertile men. Numerous sex chromosome abnormalities were found more often in infertile men, whereas structural sex chromosomal abnormalities were found more often in infertile women. Chromosomal translocations were detected in 0.99% of infertile cases. The incidence of chromosomal polymorphism in 504 primer infertile cases was found to be 8.13% as higher than that seen in general population. The incidence of chromosomal polymorphisms was 6.91% for women and 9.05% for men. In microdeletion analysis of Y chromosome, AZF region microdeletions were detected at 2.08% of 144 infertile men. Conclusion: It is thought that the evaluation of cytogenetics and Y chromosome microdeletion of cases with primary infertility diagnosis in our department between 2011 and 2016 years will contribute to the formation of data for infertility etiology in our country and the literature.
Keywords: Infertility; Chromosomal abnormalities; Y chromosome